STRATEGI PEMASARAN KEPALA MADRASAH UNTUK MENINGKATKAN JUMLAH SISWA DI MIN 16 ACEH BARAT - M. Lidan; Iswandi; Rahman, Saiful (Program Studi Manajemen Pendidikan Islam, 2025)
Abstrak The purpose of this study is to develop a marketing strategy for Madrasahs in increasing student interest. This study is limited to the product creation stage. Data collection uses documentation studies, observations, and in-depth interviews. Data validation is carried out by triangulation of sources and techniques. Data analysis techniques use the Miles and Huberman Model (interactive model): data reduction, data presentation, and drawing conclusions/verification. The results of this study: 1) the strategy implemented is to use a promotional strategy by distributing brochures and/or presentations to the determined Kindergarten Madrasahs, by holding annual activities such as AZKIA, this activity is followed by Kindergarten Madrasahs around MIN 16 West Aceh. 2) The obstacles and lack of marketing strategies implemented by this Madrasah in increasing student interest are that time management is not yet appropriate, the committee is not active enough, the foundation has not been involved, the distribution of brochures is not effective enough, marketing is not extensive enough, it does not yet have a Madrasah marketing strategy document, and it has not been able to ensure and communicate that the services offered are relevant to the needs of the community, and 3) The product produced is a Madrasah marketing strategy based on the Delta Model in attracting student interest: Keywords: Delta Model, Madrasah Marketing Strategy, Student Interest